Adriana Boscaro, Sixteenth Century European Printed Works on the First Japanesse Mission to Europe. A Descriptive Bibliography. E. J. Brill Leiden, 1973. 196 pp. - O. M., M. (Estudios de Asia y África, 1974)
-